Developing Reading Comprehension Materials Based on Outcome Based Education (OBE) For Eleventh Grade Students in the SMK Al-Washliyah 12 Sei Rampah - Dara, Febri Risma; Arfanti, Yulia; Risnawaty, Risnawaty; Asnawi, Asnawi (PT Inovasi Pratama Internasional, 2025)
This research and development (R&D) study aimed to develop, validate, and test the effectiveness of Outcome-Based Education (OBE) based reading comprehension materials for eleventh-grade students. Recognizing that reading comprehension is a critical yet challenging skill, this study addressed the need for more creative and effective teaching methods. OBE, which focuses on organizing the educational system around essential outcomes students must achieve, was employed as the foundational framework. The study followed the Borg & Gall R&D cycle. The population was students of SMK AL WASHLIYAH 12 SEI RAMPAH, with a sample of 15 students from class XI-1 selected as the experimental group. Data were collected through literacy studies, interviews, observations, group discussions, and documentation. Material validation was analyzed using descriptive quantitative techniques, resulting in an average validity score of 4.1, indicating a